An Novel Selective Image Encryption Algorithm For Networked Visual Inverted Pendulum⁎The work was supported by the National Science Foundation of China under Grant Nos. 61773253, 61473182, 61833011, 111 Project under Grant No. D18003. Issue 5 (2020) - Xing, Rui; Du, Dajun; Zhang, Changda
Abstract: The inverted pendulum image may be subject to various cyber attacks in the networked inverted pendulum visual servo control system (NIPVSCS), how to ensure the safe and efficient transmission of image data is a challenging issue. To solve this problem, this paper proposes a novel selective image encryption algorithm. First, since the encrypted inverted pendulum image will bring long computing time that makes the system performance worse, the image is scaled by using the bilinear difference method to initially reduce the amount of image data. Second, to further improve the computation speed to meet the real-time requirement of the NIPVSCS, Hough transform is employed to determine the swing rod of inverted pendulum image, and the encrypted area is set to further reduce the calculation complexity. Third, according to the key area, chaotic map is used to generate a small number of random rows and columns, which are cyclically shifted to break the strong correlation of adjacent pixels, then the XOR operation is used to mask the pixel values. Finally, simulation experiments confirm the feasibility and effectiveness of the proposed method.